Literatur Review: Perbandingan Hasil Diagnosis Laboratorium IgM, IgG SARS-CoV-2 Metode ELISA Dan ICT - Nada Farida (UPPM Poltekkes Kemenkes Ternate, 2022)
Background: The use of COVID-19 test kit depends on the sensitivity and specificity to detect and provide an accurate COVID-19 diagnosis. Currently, there are many serology tests detecting Antibody of SARS-CoV-2, that the evidence for its accuracy is still being studied through various evidence research. Purpose: Compare the sensitivity and specificity of the ELISA and ICT method for IgM, IgG SARS-CoV-2 detection. Method : literature review with Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) statement guideline. 10 out of 176 studies were obtained from searches which are carried out in PubMed, Science Direct and Google Scholar between October and December 2020. Articles were independently screened by title, abstract and full-text using the PICOS framework and critically appraised using JBI Critical Appraisal Tools. Findings were descriptively analyzed. Result : , Comparison of ELISA and ICT sensitivity in detecting IgM, IgG SARS-CoV-2 was 76,3%, 77,3% and ICT method : 53,9%, 64,8%. While the specificity of the ICT method was 96,2%, 98,1% and ELISA method : 94%, 97,1%. Conclusion: The sensitivity of IgM, IgG SARS-CoV-2 detection using ELISA method was higher than the ICT method. Conversely, the specificity of the ICT method (97.1%) is higher than the ELISA method (95.5%)